2022
DOI: 10.1101/2022.12.19.22283671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of the foreign language on cognitive reappraisal during exposure to a phobic stimulus

Abstract: The foreign language effect shows that emotional reactivity is reduced when we use a second language instead of our native one to address different situations. The present study aims to test whether the use of cognitive reappraisal could be influenced by the participants language (native/foreign). For this purpose, a sample of 60 participants with subclinical phobia to cockroaches was exposed to several phobic and neutral pictures while they used cognitive reappraisal in their native or in a foreign language. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In this regard, a study conducted by García-Palacios et al (2018) showed that conditioning of fear was lighter in a foreign language in comparison to the native one suggesting that the foreign language context can help to reduce emotional reactivity and take distance from the situation. Also, Ortigosa Beltrán et al (in review) explored the effect of a foreign language during cognitive reappraisal. They showed that using a foreign language could be advantageous in reducing negative emotionality produced by phobic stimuli through this emotion regulation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a study conducted by García-Palacios et al (2018) showed that conditioning of fear was lighter in a foreign language in comparison to the native one suggesting that the foreign language context can help to reduce emotional reactivity and take distance from the situation. Also, Ortigosa Beltrán et al (in review) explored the effect of a foreign language during cognitive reappraisal. They showed that using a foreign language could be advantageous in reducing negative emotionality produced by phobic stimuli through this emotion regulation strategy.…”
Section: Introductionmentioning
confidence: 99%